Analisis Manajemen Keuangan Pada Toko Ritel Angkasa Mart di Kota Pekanbaru - Muhammad Rafi Fadhilah; Ruhul Fitrios (E-Bisnis : Jurnal Ilmiah Ekonomi dan Bisnis, 2026)
This study aims to determine the financial management practices implemented at Angkasa Mart retail stores in Pekanbaru City, including financial planning, recording, reporting, and control. The background of this study is based on the ineffectiveness of financial management implementation and the existence of fraud that causes financial losses. In this study, a qualitative approach was used with data collection techniques through interviews, observation, and documentation. The research findings indicate that financial planning has been implemented. Financial recording has also been implemented, but there is no integration between the manual system and recording using accounting software, potentially causing errors in data management. Financial reporting is prepared using Excel and accounting software, which has the potential to cause errors in reporting. On the other hand, financial controls have been implemented, but there are still weaknesses in the internal control system, fraud prevention, and financial performance monitoring that create fraud. The results of this study indicate that financial management practices at Angkasa Mart are not optimal, especially in system integration, financial report preparation, and improvements in financial controls to improve financial management practices